OPTIMIZING HEALTH SERVICE MANAGEMENT IN UMRAH TOUR OPERATORS: A RETROSPECTIVE ANALYSIS - Yaltafit Abror Jeem; Muhammad Kharisma; Yayuk Fathonah; Arif Budi Santoso; Wahyu Agung Sudrajat (Multazam : Jurnal Manajemen Haji dan Umrah, 2026)
Private Umrah tour operators (PPIU) rarely utilize morbidity data for health service management. This retrospective descriptive study analyzes 783 medical consultations from a PPIU between October 2024 and February 2025 to optimize health logistics and operational strategies. The analysis reveals that morbidity is dominated by acute respiratory infections (38.4%) and musculoskeletal disorders (28.1%), followed by hypertension/cardiovascular issues (10.2%), gastrointestinal disorders (8.5%), and dermatitis (5.8%). A distinct seasonal peak occurred during the winter months (December–January). Furthermore, elderly pilgrims (>60 years) demonstrated a significantly higher risk of fatigue-induced hypertension. These findings emphasize that Umrah health needs are highly predictable. The study concludes that PPIUs must shift from reactive care to proactive, data-driven health logistics. This involves integrating internal morbidity surveillance into pharmaceutical forecasting, adjusting medical supplies seasonally, and implementing targeted preventive programs for high-risk groups. Training tour leaders to manage pilgrim fatigue is identified as a critical operational strategy to enhance logistical efficiency, pilgrim safety, and service competitiveness.